(untitled) (Ameghiniana, 2013)
Monticutipora argentina was first described by Kayser in 1876 and included in the Phylum Bryozoa. Although mentioned in several paleontological papers, this organism was never reviewed in a taxonomic way. New collected material allows a reexamination of the systematic position of M. argentina suggesting its separation from this phylum. The new genus Fiscella is erected to include F. argentina (Kayser) and the new species F. flabelis. A possible relationship of these organisms with aseptate corals and calcareous algae is discussed. Probable affinities with gastropod’s opercula are also considered.